2018
DOI: 10.3390/su10010094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Energy Consumption on Air Quality in Jiangsu Province of China

Abstract: Air quality has become an important sustainability concern for China's highly developed economic regions. Taking Jiangsu Province as a case, this study investigates the effect of energy consumption on air quality when both considering and not considering control variables, such as industrial structure, energy consumption structure and energy efficiency from 2006 to 2015 and further explores the influence of the related policies on air quality and the relationship between energy consumption and air quality. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Secondly, studies performed at the regional/provincial level were all resourceful, including those on Northwest China [20], Yunnan [21], Guangdong [22][23][24], Jiangsu [25,26], Shanghai [27], Chongqing [28,29], and Xinjiang [30]. The factors found to have the greatest effect on carbon emissions were economic activity [20], investment [21], energy density [21,23,24,26], economic growth [23,24], export [21], population scale [24], energy efficiency [20], technical progress [24], industrial structure [22,23,26], and energy Sustainability 2019, 11,7008 3 of 20 mix [24,26]. For example, Dong et al [21] analyzed the energy-related carbon emissions of five provinces in Northwest China from 1995 to 2012 (Shaanxi, Ningxia, Qinghai, Gansu, and Xinjiang) and found that the effect of economic activity produced a significant impact on increased carbon emission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondly, studies performed at the regional/provincial level were all resourceful, including those on Northwest China [20], Yunnan [21], Guangdong [22][23][24], Jiangsu [25,26], Shanghai [27], Chongqing [28,29], and Xinjiang [30]. The factors found to have the greatest effect on carbon emissions were economic activity [20], investment [21], energy density [21,23,24,26], economic growth [23,24], export [21], population scale [24], energy efficiency [20], technical progress [24], industrial structure [22,23,26], and energy Sustainability 2019, 11,7008 3 of 20 mix [24,26]. For example, Dong et al [21] analyzed the energy-related carbon emissions of five provinces in Northwest China from 1995 to 2012 (Shaanxi, Ningxia, Qinghai, Gansu, and Xinjiang) and found that the effect of economic activity produced a significant impact on increased carbon emission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2016, Yale University published the Environmental Performance Index (EPI) report, which ranked China as of last in the world, just before Bangladesh, based on air quality assessment [52,53]. Jiangsu Province is an economically developed province in eastern China, having dense metropolises and large rural areas, with urban constructions, high traffic volumes, industrial production, and crop residue burning, which all add significant amounts of pollutants into the atmosphere, resulting in noticeable air pollution in the province [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, aerosol products have been widely evaluated over land, including the American continents [54,55] and South Asia [56], using the MODIS MAIAC algorithm. Although a few validation studies have also been conducted over China [57][58][59], the performance of the MAIAC algorithm is still unclear in China due to high levels of aerosol loading, and heterogeneity. Due to China's rapid social and economic development in recent years, the country is in line with serious aerosol pollution.…”
Section: Introductionmentioning
confidence: 99%